HBR's 10 must reads on ai, analytics, and the new machine age - Wilson, H. James; Daugherty, Paul; Davenport, Thomas H., 1954-; Porter, Michael E.; Compton, Shawn; Schnaubelt, Teri (Gildan Audio, 2019)
Machine learning and data analytics are powering a wave of groundbreaking technologies. Is your company ready'We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you understand how these technologies work together, how to adopt them, and why your strategy can't ignore them. In this book you'll learn how: data science, driven by artificial intelligence and machine learning, is yielding unprecedented business insights; blockchain has the potential to restructure the economy; drones and driverless vehicles are becoming essential tools; 3-D printing is making new business models possible; augmented reality is transforming retail and manufacturing; smart speakers are redefining the rules of marketing; and humans and machines are working together to reach new levels of productivity.